The New Frontiers in Neurodegenerative Diseases Treatment: Liposomal-Based Strategies - Cascione, Mariafrancesca; De Matteis, Valeria; Leporatti, Stefano; Rinaldi, Rosaria (Frontiers in Bioengineering and Biotechnology, 2020)
In the last decade, the onset of neurodegenerative (ND) diseases is strongly widespread due to the age increase of the world population. Despite the intensive investigations boosted by the scientific community, an efficacious therapy has not been outlined yet. The drugs commonly used are only able to relieve symptom severity; following their oral or intravenous administration routes, their effectiveness is strictly limited due to their low ability to reach the Central Nervous System (CNS) overcoming the Blood Brain Barrier (BBB). Starting from these assumptions, the engineered-nanocarriers, such as lipid-nanocarriers, are suitable agents to enhance the delivery of drugs into the CNS due to their high solubility, bioavailability, and stability. Liposomal delivery systems are considered to be the ideal carriers, not only for conventional drugs but also for neuroprotective small molecules and green-extracted compounds. In the current work, the LP-based drug delivery improvements in in vivo applications against ND disorders were carefully assessed.